Analisis Pengawasan Partisipatif Badan Pengawas Pemilu di Kabupaten Ogan Komering Ilir - Irawan, Hadi; Idris, Umiyati; Berlian, Ong (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to analyze the participatory supervisison of the election supervisory body in Ogan Komering Ilir Regency. This research is a descriptive research with a qualitative approach. The data used is based on its type, namely quantitative and qualitative, while based on the source is primary data and secondary data. The data collection instruments used were observation, interviews and documentation. The informantsin this study were the chairman and members of the Bawaslu of Ogan Komering Ilir, secretarial employees of the OKI Bawaslu and community elements in Ogan Komering Ilir Regency. Data analysis ia a qualitative analysis with an interactive model, based on the results of research and discussion on participatory supervision. The Election Supervisory Body in Ogan Komering Ilir Regency has been implemented although there are still shortcomings and not optimal. As for the obstacles, the role of Bawaslu in carrying out transparent and fair election supervision is not only limited to supervisors but also as judges who decide cases, the lack of publik awareness and knowledge about elections and the widespread and massive violations that occur.